2005
DOI: 10.1359/jbmr.050707
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Bone Growth Patterns Defines Adult Mouse Bone Fragility

Abstract: Femoral morphology and composition were determined for three inbred mouse strains between ages E18.5 and 1 year. Genotype-specific variation in postnatal, pubertal, and postpubertal growth patterns and mineral accrual explained differences in adult bone trait combinations and thus bone fragility.Introduction: Fracture risk is strongly regulated by genetic factors. However, this regulation is generally considered complex and polygenic. Therefore, the development of effective genetic-based diagnostic and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
135
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(145 citation statements)
references
References 36 publications
10
135
0
Order By: Relevance
“…The preservation of the total subperiosteal area could have maintained the bone strength; however, the calculated stress and Young's modulus values were significantly lower in the experimental groups. Tthe ash fraction of the tibial diaphysis, a measure of mineral content in bone was not different between groups; not a surprising result as Price et al (2005) (18) reported that the variability in ash content is established early in life and thus is not a major accommodation strategy to alter stiffness during pubertal delay. Factors such as collagen cross-linking, mineral crystal size, collagen fiber orientation and microstructure organization may affect bone strength (35).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The preservation of the total subperiosteal area could have maintained the bone strength; however, the calculated stress and Young's modulus values were significantly lower in the experimental groups. Tthe ash fraction of the tibial diaphysis, a measure of mineral content in bone was not different between groups; not a surprising result as Price et al (2005) (18) reported that the variability in ash content is established early in life and thus is not a major accommodation strategy to alter stiffness during pubertal delay. Factors such as collagen cross-linking, mineral crystal size, collagen fiber orientation and microstructure organization may affect bone strength (35).…”
Section: Discussionmentioning
confidence: 84%
“…The relative cellular activity on the periosteal and endocortical bone surfaces specifically during puberty affects bone size, a critical element of bone strength (18). Increased estrogen levels during puberty have been hypothesized to inhibit periosteal modeling in females (19) and thus result in smaller and weaker bones compared to males.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because the amount of voluntary cage‐wheel running is expected to vary among exercised mice, we tested for associations between distance run and each of the morphological and mechanical properties to identify parameters that may be sensitive to the amount of cage‐wheel activity during growth. Though this study does not specifically test for in situ tissue‐level strain differences in the femora of growing A/J and B6 mice, we anticipate that mechanical strain levels will be similar between the two running mouse strains because they both have similar body mass and long bones of near equivalent stiffness 13. Thus, any differential phenotypic response to voluntary cage‐wheel running should be more applicable to either a difference in the number of loading cycles (ie, wheel revolutions) sustained, or may reflect a difference in the normal strain distribution pattern between these two mouse strains.…”
Section: Introductionmentioning
confidence: 99%
“…The Lewis and Fischer inbred rat strains have been used as a model of human aging-related traits [10][11][12] including an intercross genome screening study of bone properties [13]. The power of the mouse as a genetic tool has been utilized to uncover genes whose normal allelic variation regulates BMD and other skeletal traits such as bone geometry, microarchitecture and strength [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. An inbred strain survey is a useful step in a thorough genetic analysis of a complex quantitative trait like BMD in mice [23].…”
Section: Introductionmentioning
confidence: 99%